Validation of new invasive digital hemoglobinometer for hemoglobin estimation as point-of-care device among pregnant women in a facility setting India - khanam, Areeba; Chandra, Ankit; Achary, Thejas; Vohra, Kashish; M, Aravind; Singh, Archana; Yadav, Kapil (Indian Journal of Community Health, 2024)
Background: Anemia poses a significant health challenge for pregnant women (PW), and accurate and timely diagnosis is essential for effective management. Objective: The objective was to assess the diagnostic validity of the new digital hemoglobinometer for hemoglobin against laboratory-based hematology autoanalyzer among PW. Methodology: The study was conducted at a secondary-level healthcare facility among 204 pregnant women to be sampled conveniently, their sociodemographic and iron intake data collected, and hemoglobin levels assessed using a digital hemoglobinometer (Device A) and a hematology analyzer. Specificity, sensitivity, PPV, NPV, diagnostic accuracy, and method agreement were evaluated via Bland-Altman analysis and Lin's concordance correlation coefficient. Results: The proportion of anemia using the Device A was 64.7% while the hematology analyzer reported a proportion of 52.9%. Device A showed a sensitivity of 97.22%, specificity of 80.30%, and diagnostic accuracy of 86.3%, with substantial agreement indicated by Cohen's kappa coefficient (kappa = 0.72) and the weighted kappa coefficient for different grades of anemia was 0.67. Bland-Altman analysis revealed a mean difference (bias) of -0.28 (± 0.5) between the two methods, with limits of agreement at -1.24 and 0.68. Lin's concordance correlation coefficient of absolute agreement was 0.91. Conclusion: The DH showed high sensitivity and diagnostic accuracy for anemia detection in PW, with substantial agreement with the hematology analyzer. It offers a convenient and rapid alternative for POC hemoglobin estimation in resource-constrained settings.